2019
DOI: 10.3390/ijms20153671
|View full text |Cite
|
Sign up to set email alerts
|

Rapid or Slow Time to Brain Death? Impact on Kidney Graft Injuries in an Allotransplantation Porcine Model

Abstract: The use of donors deceased after brain death (DBD) with extended criteria in response to the shortage of grafts leads to the removal of more fragile kidneys. These grafts are at greater risk of not being grafted or delayed function. A better knowledge of the pathophysiology of DBDs would improve this situation. There is a difference between the results from animal models of DBD and the clinical data potentially explained by the kinetics of brain death induction. We compared the effect of the induction rate of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…We previously demonstrated that ANOR could counteract DCD-induced IR lesions [22]. Herein, we investigated the hypothesis that DCD organs, when ANOR was used, were better than marginal organs and actually non inferior to standard DBD [24]. We tested this in a fully controlled preclinical model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously demonstrated that ANOR could counteract DCD-induced IR lesions [22]. Herein, we investigated the hypothesis that DCD organs, when ANOR was used, were better than marginal organs and actually non inferior to standard DBD [24]. We tested this in a fully controlled preclinical model.…”
Section: Discussionmentioning
confidence: 99%
“…Brain death was reached by progressive insufflation of a balloon in the extradural space until a flat electroencephalogram was obtained [24]. Reanimation was maintained for 4 h before organ collection.…”
Section: Brain Death Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to Akt/GSK3β signaling pathway, Sirtuin 1 (SIRT1) signaling pathway can also increase Nrf2 transcription by deacetylating PGC1-α. 11,12 SIRT1, as the most studied enzyme among the 7 deacetylases in the Sir family, is widely present in various cells of the body and is closely related to the energy metabolism and reduction state of cells. 13,14 It is a new potential therapeutic target for diabetic nephropathy.…”
Section: Introductionmentioning
confidence: 99%
“…These strategies can be applied either immediately after organ procurement or after static cold storage (SCS). In any case, the oxygenation of the organs is an unsolved problem that attracts the interest and efforts of researchers in the field [26,27].…”
mentioning
confidence: 99%